The responsible business : reimagining sustainability and success - Sanford, Carol, 1942- (San Francisco, CA : Jossey-Bass, 2011)
'From innovation to shareholder development, this groundbreaking book offers guidelines for becoming a responsible corporation Strategic Corporate Responsibility shows how to implement a systemic and integrative approach for bringing Corporate Responsibility (CR) into the organization as a whole, embedding CR thinking into the entire business. The book offers a strategic model that fills the need to create corporate citizens working on the regeneration of societal and planetary health while growing a healthier business. It provides a framework for building a consciousness infrastructure throughout an organization and applying a living systems view to the business and its stakeholders. Outlines the core principles of corporation responsibility and offers a framework for implementation of a CR program Shows how to engage all stakeholders in enhancing a company's ability to manage itself responsibly Includes real business examples and from a variety of companies-global and local, consumer and retail as well as extractive manufacturing The book demonstrates, through illustrative examples, how to makes CR integral to all aspects of the business as an engine for innovation as well as renewed spirit and purposefulness.'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Social responsibility of business; Corporate culture; Strategic planning